REPORT OF THE COMMITTEE ON MANAGEMENT ACCOUNTING. - Bower, James B.; Pressler, Stanley A.; Rickard, E.B.; Welsch, Glenn A.; Brummet, R. Lee (The Accounting Review, 1960)
The article presents information about the report of the 1959 Committee on Management Accounting. The 1959 Committee has directed its efforts toward an amplification of this view of the nature and significance of management accounting by stating in more definite terms the functions to be performed by accounting in a business entity organized for profit, and by a listing of the major problem areas in which management accounting is of prime importance. The role of management accounting is to provide the management of a business with analyses and evaluations to assist in the fulfillment of this basic responsibility for effectively planning and controlling profits and investments. It is a service which is oriented toward the evaluation of the financial soundness of the future operating plans and programs of the enterprise and the anticipated profit consequences of alternative courses of action. The Committee believes that a significant need exists for a better and more general awareness of the proper role of management accounting in a well-managed business.